Determinants of customers’ intention to adopt green banking technology services within Islamic banks of the United Arab Emirates - Bouteraa, Mohamed (2022)
Green Banking (GB) is encouraging environment-friendly practices and reducing the carbon footprint from banking operations by promoting paperless financial services based on the intensive use of technology. However, the adoption level of GB technology remains unsatisfactory among bank customers in the United Arab Emirates. This study explored the dimensions of individual, technological, organisational, environmental and religious determinants of the phenomenon. The study further extended the Unified Theory of Acceptance and Use of Technology (UTAUT) by examining the identified dimensions’ effect on customers’ intention to adopt GB technology, alongside the moderating role of gender, age and experience. The exploratory sequential mixed-method design was deployed in this study. A preliminary semi-structured interview was conducted among ten bank professionals to explore the dimensions of the predetermined determinants. The qualitative findings using the Thematic Content Analysis (TCA) revealed the related dimensions affecting customers’ adoption of GB technology. The developed research model was validated via a cross-sectional survey of 332 Islamic bank customers. The quantitative results using the Partial Least Squares Structural Equation Modelling (PLS-SEM) confirmed the significant impact of performance expectancy, facilitating condition, customer awareness, personal innovativeness, perceived benefit, system quality and bank reputation on customers’ intention to adopt GB technology. The moderating results using Multi-Group Analysis (MGA) revealed that only gender affects the relationship between performance expectancy and customers’ intention to adopt GB technology. This study has significant theoretical, methodological and practical contributions to enhance the understanding of customers’ intention to adopt GB technology. The study could also assist bankers in designing effective strategies to diminish customers’ resistance of GB technology through the applicability of the newly proposed factors. Reflecting the moderating influence of gender provides an in-depth clarification for policy-makers in pitching GB technology to relevant customers with minimal waste of resources by formulating distinct strategies for dynamic demographic segments.